Improving biodiesel oxidative stability using antioxidants: An insight into the research trends and future prospects from a bibliometric approach - Usman Bello; Haruna Adamu; Shafirah Samsuri; Hamza Ibrahim; Mohammad Qamar (Results in Engineering)
This review highlights the current status and future directions for improving biodiesel oxidative stability using antioxidants as a crucial step toward ensuring its long-term sustainability and practical application. The bibliometric study collected and analyzed 1860 documents from the SCOPUS database published between 2014 and 2024. Keyword analysis highlights terms like ''antioxidants'' and ''feedstocks'', including fats and oils, plant seeds, and plant extracts, emphasizing the critical role of feedstock types as principal drivers for initiating oxidation reactions. A co-country analysis identified ''China'' and ''India'' as top contributors, with 11,653 and 9298 citations, respectively, showcasing their strong research commitment to sustainable bioenergy. ''Chemical Reviews'' was tabled as the most-cited journal (4396 citations) and ''Yaakob et al., 2014'' as the most-cited author (449 citations) within the review period, underscoring the researchers’ active involvement in the field. While natural antioxidants have demonstrated superior antioxidative potential compared to their synthetic counterparts owing to greater solubility, lower cost, and higher potency at lower concentrations, their efficacy can be further enhanced through synergistic combinations. In contrast, the application of nanotechnology-based antioxidants in biodiesel stabilization remains in its infancy, presenting promising opportunities for further exploration. Finally, this study offers valuable insights into research trends, existing gaps, and future directions for researchers, policymakers, and industry stakeholders committed to enhancing biodiesel stability and advancing sustainable energy solutions.